2021
DOI: 10.5902/1983465930537
|View full text |Cite
|
Sign up to set email alerts
|

Negócios sociais e âncoras de carreira: um estudo sobre o envolvimento dos estudantes universitários

Abstract: Purpose: the objective of this study is to analyze the career anchors (Schein, 1974) of university students involved in social activities. Design/methodology/approach: we chose a quantitative descriptive approach, with the application of a questionnaire to 68 young students participating in the CHOICE ambassador program. Findings: results showed the predominance of the service and dedication to a cause anchor, and the relevance of acting in student and volunteer organizations. The career anchor acts as an infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Fogaça L.S. et al [12] studied how career anchors and social business are interconnected, the sample consisted of 68 young students of the University of Sao Paulo, Brazil. Sheveleva A.M. et al [13] found out how career anchors are related to the motives of educational and labor activity of students who receive the qualification of a teacherpsychologist, the sample consisted of 114 people -students of the Southern Federal University, Rostov-on-Don, Russian Federation.…”
Section: Introductionmentioning
confidence: 99%
“…Fogaça L.S. et al [12] studied how career anchors and social business are interconnected, the sample consisted of 68 young students of the University of Sao Paulo, Brazil. Sheveleva A.M. et al [13] found out how career anchors are related to the motives of educational and labor activity of students who receive the qualification of a teacherpsychologist, the sample consisted of 114 people -students of the Southern Federal University, Rostov-on-Don, Russian Federation.…”
Section: Introductionmentioning
confidence: 99%